A construct-psychological approach to the measurement of chill-sensations - Kunkel, Markus; Pramstaller, Christopher; Grant, Phillip; Georgi, Richard von; Justus Liebig University Giessen (My University, 2008)
Chills, meaning strong emotional responses to music, have to date been almostonly examined within experimental settings. Within the pilot-study athand the first psychometric inventory for the measurement of subjectivechill-sensations (MRCQ) was developed using two successive samples. Herethrough is should be possible to assess intra- and interindividual differencesreliably and in a standardized fashion outside of a laboratory situation. Thefirst study descriptively examined open questions on chill-sensations on asample of n=151. A second study (n=108) examined the existence of latentdimensions within the pool of items constructed in the first study. Factoranalyses yielded five facettes of chill-sensations: positive, physiological,motor and social-cognitive reactivity as well as general disorientation. Allfive scales reached sufficient reliability for their individual item numbers.Correlations with other inventories (NEO-ffi, IAAM) show that chill-sensationsare closely linked to high extraversion, openness to experience andemotional stability. The results, however, appear to be indicative of differencesbetween the sexes. On a whole the results support existing researchand theoretical models, but there are also some important differences. TheMRCQ offers a possibility of researching chills in non-experimental musicsciences.
Keywords: ddc:780